Assessment of Empathy Life Skill among Adolescents. (1st April 2016) - Kaur, Amandeep; Pathania, Raj
Abstract: The present study entitled was undertaken with the specific objectives viz. (i) to assess the empathy skills of adolescents and (ii) to compare these skills among male and female adolescents. The data were collected from two randomly selected blocks (Baijnath and Panchrukhi) of Kangra district of Himachal Pradesh, India. A total of 120 adolescents (60 male and 60 female) of age 15-18 years were selected from the three schools of each block. To collect the required data from the respondents, an interview schedule, covering measures of empathy was prepared. The data was analyzed statistically using frequency, percentages and t-test. The results revealed that maximum respondents possessed medium level of empathy. Significant differences were found in overall empathy skills of male and female respondents. Likewise, significant differences were found in mean values of perspective taking, empathic concern and personal distress between male and female respondents, whereas non-significant difference was found in fantasy measure of empathy.